Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Ask your questions and receive detailed answers from professionals with extensive experience in various fields. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Answer:
(2,-1)
Step-by-step explanation:
The ys in both questions are isolated on one side of the equation in both. The numerical coefficient of both is 1. Therefore you should equate the the left side of each equation to the other left side. The solution is the easiest one to solve because there is only 1 unknown on both sides.
4x - 9 = x - 3 Subtract x from both sides.
4x-x - 9 = -3 Combine
3x -9 = - 3 Add 9 to both sides
3x - 9+9 = - 3+9
3x = 6 Divide by 3
3x/3 = 6/3
x = 2
===============
Now use the second equation to solve for y
y = x - 3
y = 2 - 3
y = -1
==============
The solution is (2,-1)
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.